Uso indiscriminado de antibióticos en la prevención de infecciones como precursor de resistencia bacteriana (monografía) (2023)
According to the Center for Disease Control, or CDC of the United States, more than 2.8 million antibiotic-resistant infections occur in the United States each year, and more than 35,000 people die as a result of them. (CDC, 2019) Although antibiotics have helped lethal diseases be easily treated and have contributed to advances in other fields of medicine such as organ transplants and chemotherapy, their unregulated use can have serious consequences for human and animal health.